2018
DOI: 10.3390/en11030664
|View full text |Cite
|
Sign up to set email alerts
|

Algal Biomass from Wastewater and Flue Gases as a Source of Bioenergy

Abstract: Algae are without doubt the most productive photosynthetic organisms on Earth; they are highly efficient in converting CO 2 and nutrients into biomass. These abilities can be exploited by culturing microalgae from wastewater and flue gases for effective wastewater reclamation. Algae are known to remove nitrogen and phosphorus as well as several organic contaminants including pharmaceuticals from wastewater. Biomass production can even be enhanced by the addition of CO 2 originating from flue gases. The algal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 212 publications
(305 reference statements)
1
38
1
3
Order By: Relevance
“…One of them was dried and the other one was an ash form. P. animale is prokaryotic blue green algae and its biomass can be easily and economically produced (Lage et al, 2018) and the results of this study supported that the algal biomass can be used as efficient biosorbent for treatment of textile wastewater.…”
Section: Molecular Formula C26h21n5na4o19s6supporting
confidence: 62%
“…One of them was dried and the other one was an ash form. P. animale is prokaryotic blue green algae and its biomass can be easily and economically produced (Lage et al, 2018) and the results of this study supported that the algal biomass can be used as efficient biosorbent for treatment of textile wastewater.…”
Section: Molecular Formula C26h21n5na4o19s6supporting
confidence: 62%
“…The capture of CO 2 as a source of carbon in the production of microalgae biomass has also been considered to be an option for reducing these emissions. Due to their high photosynthetic capacity, as compared to terrestrial plants [9], they are able to capture up to 1.7 kg of CO 2 per kilogram of biomass produced [10]. Microalgae accumulate significant amounts of fats, carbohydrates, proteins, and other compounds of great economic importance, such as pigments and vitamins [11][12][13].…”
Section: Microalgaementioning
confidence: 99%
“…Moreover, while some researchers [15][16][17] argue that the use of biofuels and bioenergy have a strong impact on the reduction levels of CO 2 , other economists [18][19][20] conclude that resources productivity and energy efficiency have a higher impact on CO 2 emissions. Nevertheless, while some authors [21][22][23] argued that bioenergy productivity and biofuel production have a direct and significant impact on decreasing the levels of CO 2 emissions, other researchers [24,25] concluded that population and urbanization levels have a significant and negative impact on decreasing the levels of CO 2 emissions. An assessment [24] of the European renewable energy source (RES) trajectory towards 2020, starting from historical values and through common scientific methods, laid down a new approach to evaluate RES performance in Europe.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%